Characterization of short-term storage of the semen of Trachelyopterus galeatus (Siluriformes: Auchenipteridae) incorporating dimethylsulphoxide (dmso) to the diluent - França, Caroline Lopes; Castro, Jorgélia De Jesus Pinto; Silva, João Mandú da; Santos, Ricardo Pinto; Castro, Jonatas Da Silva; Teixeira, Erivânia Gomes (Aquaculture Research, 2022)
The purpose of this study was to evaluate the effect of adding dimethylsulphoxide cryoprotectant (DMSO) to the diluent used with refrigerated semen of Trachelyopterus galeatus. Semen samples were analysed for colour, volume, pH, motility rate, concentration and morphological changes. Semen, cooled to 4°C, were diluted in Hanks Balanced Saline Solution (HBSS) and HBSS + DMSO at concentrations of 2.5%, 5.0% and 10% and evaluated at time intervals of 0; 12 h; 24 h; 36 h; 48 h; 60 h and 72 h. The fresh semen (undiluted) was white in colour with a milky appearance, had pH (6 ± 0), motility rate of 90.6 ± 13.4% and concentration of 2.7 ± 0.7 × 106 cells ml−1. Morphological analysis demonstrated that 70.6 ± 0.65% of sperm were normal, while 29.4 ± 1.5% presented some change, such as a bent tail (13.02 ± 0.32%) or a strongly bent tail (4.45 ± 0.13%). Chilled fresh semen were viable for 48 h when they had a motility rate of 35 ± 8.6%. Treatments in concentrations of 2.5% and 5.0% showed motility rates of 30 ± 4% and 27.5 ± 7.5%, respectively, after 60 h of exposure, and were considered efficient. This protocol is therefore indicated for semen conservation in T. galeatus.
Keywords: Sperm Motility; Cryopreservation; Spermatozoa